Development of New Chip Products from Brewer’s Spent Grain - Reann Garrett; Danielle Bellmer; William McGlynn; Patricia Rayas-Duarte (Journal of Food Quality)
Brewer’s spent grain (BSG) is a processing waste generated in large quantities by the brewing industry. It is estimated that over 38 million tons of BSG is produced worldwide each year and is usually used as animal feed, composted, or thrown into landfills. BSG contains valuable nutritional components, including protein, fiber, and antioxidants. Due to its brittle texture, strong nutty flavors, and dark color profiles, BSG has seen limited use in food products for human consumption. The objective of this study was to develop a palatable chip product that maximized the level of inclusion of BSG. Chips were produced that contained BSG levels ranging from 8% to 40%, and the physical and sensory properties of the chips were evaluated. Spent grain samples were provided by Iron Monk in Stillwater and were dried at a low temperature and milled into flour for use in the chip formulation. BSG chips were evaluated for water activity, color, and texture (fracture force). An informal sensory evaluation was conducted to evaluate flavor, texture, and probability of purchase using a 5-point hedonic rating scale. Results showed that there were no significant differences in the texture of the chips containing different levels of BSG. The color measurements showed no significant differences between L∗ and a∗ values for the chips containing different inclusion levels of BSG, but there were some differences in the b∗ values. Results from the sensory evaluation showed that consumers preferred the texture of chips with 40% BSG over chips with 8% BSG, and they were also more likely to purchase the 40% BSG chips. There were no significant differences in flavor among the chips containing different inclusion levels of BSG. These results suggest that, for a chip-type product, BSG inclusion levels up to 40% are possible with positive consumer responses. Development of an alternative value-added product represents an opportunity for breweries nationwide to turn a processing waste into a future asset.